Clinicopathological and dermoscopic correlation of pigmented basal cell carcinoma - Reddy, Duttala Indira; Sangaiah, Sivaramakrishnan; N. R., Vignesh; G., Sukanya (International Journal of Research in Dermatology, 2021)
Basal cell carcinoma (BCC), also known as basal cell epithelioma is the most common cutaneous malignancy affecting fair skinned individuals arising from sun exposed skin especially head and neck area. It is a slow growing tumor which rarely metastasizes. UV radiation is the most important predisposing factor. It includes mainly four variants: (a) nodular, (b) pigmented, (c) superficial BCC, (d) sclerosing or morphea form of which most common is nodular variant. Dermoscopy of pigmented BCC shows well focussed arborizing vessels which is the hallmark. The best modality of treatment is surgical excison of tumour, electrodesiccation and curettage, cryosurgery, and Mohs micrographic surgery.